2018
DOI: 10.1371/journal.pone.0193680
|View full text |Cite
|
Sign up to set email alerts
|

Broad cross-reactive IgG responses elicited by adjuvanted vaccination with recombinant influenza hemagglutinin (rHA) in ferrets and mice

Abstract: Annual immunization against influenza virus is a large international public health effort. Accumulating evidence suggests that antibody mediated cross-reactive immunity against influenza hemagglutinin (HA) strongly correlates with long-lasting cross-protection against influenza virus strains that differ from the primary infection or vaccination strain. However, the optimal strategies for achieving highly cross-reactive antibodies to the influenza virus HA have not yet to be defined. In the current study, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 55 publications
(101 reference statements)
1
50
0
Order By: Relevance
“…Seroconversion with a ≥ 4‐fold rise in HI or MN antibody titers is indicative of recent influenza virus infection or vaccination . In recent years, magnetic multiplex fluorescence microsphere immunoassays (MAGPIX) have been developed to investigate antibody profiles following influenza vaccination/infection and aid in the diagnosis of influenza . Previously, we developed a high‐throughput MAGPIX assay with serum adsorption using two ectodomain recombinant HAs (rHAs) from A(H1N1)pdm09 (A/California/7/2009, CA/09) and A/Perth/16/2009 (Perth/09, A(H3N2)) to identify novel influenza exposures when well‐paired human serum samples were available .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seroconversion with a ≥ 4‐fold rise in HI or MN antibody titers is indicative of recent influenza virus infection or vaccination . In recent years, magnetic multiplex fluorescence microsphere immunoassays (MAGPIX) have been developed to investigate antibody profiles following influenza vaccination/infection and aid in the diagnosis of influenza . Previously, we developed a high‐throughput MAGPIX assay with serum adsorption using two ectodomain recombinant HAs (rHAs) from A(H1N1)pdm09 (A/California/7/2009, CA/09) and A/Perth/16/2009 (Perth/09, A(H3N2)) to identify novel influenza exposures when well‐paired human serum samples were available .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In recent years, magnetic multiplex fluorescence microsphere immunoassays (MAGPIX) have been developed to investigate antibody profiles following influenza vaccination/ infection and aid in the diagnosis of influenza. [3][4][5] Previously, we developed a high-throughput MAGPIX assay with serum adsorption using two ectodomain recombinant HAs (rHAs) from A(H1N1) pdm09 (A/California/7/2009, CA/09) and A/Perth/ 16/2009 (Perth/09, A(H3N2)) to identify novel influenza exposures when well-paired human serum samples were available. 4 However, during novel influenza virus outbreak investigations, paired serum collection may not always be feasible, posing challenges to determine influenza virus infections through serology.…”
Section: Introductionmentioning
confidence: 99%
“…The mPlex-Flu assay was performed as described previously [7,8,12] [7,12], and the standard curve for each influenza virus strain was generated by 1:4 serially diluting STD01 for each batch of samples. 50µL of the diluted sample was added into each reaction well.…”
Section: Mplex-flu Assaymentioning
confidence: 99%
“…The influenza HA bead panel used in this study is shown in Table ??, comprising 33 separate rHAs. 50µL of bead mix was added to each well of the plate as previously described [7,8,12]. Plates were then incubated with gentle shaking for 2 hours at room temperature, and then washed (PBS + 1% Bris + 0.1% BSA).…”
Section: Mplex-flu Assaymentioning
confidence: 99%
See 1 more Smart Citation